Development and growth of larvae of the dog conch, Strombus canarium (Mollusca: Gastropoda), in the laboratory - Che Cob, Zaidi; Arshad, Aziz; Abd. Ghaffar, Mazlan; Bujang, Japar Sidik; Wan Muda, Wan Lotfi (Biodiversity Research Center, Academia Sinica, Taiwan, 2009)
Strombus canarium egg masses used in this study were collected while still underneath spawning females, and embryonic and post-hatching larval development was observed in the laboratory. Strombus canarium larvae were reared at 200 larvae/L in 2-L containers with 0.22 μm filtered seawater medium at a salinity of 30 ± 1 PSU, and fed a single algal species, Isochrysis galbana, at 1000 cells/ml. Fecundity was estimated at 48,745 ± 877 to 93,643 ± 1685 (n = 10) eggs/egg mass. The incubation time Fecundity was estimated at 48,745 ± 877 to 93,643 ± 1685 (n = 10) eggs/egg mass. The incubation time 93.34% ± 1.68% hatched, n = 3). The larvae have 2 velar lobes and 1.5 shell whorls at the time of hatching, with an average shell length of 216.77 ± 5.72 μm (n = 10). Based on prominent larval characters and visible morphological features, S. canarium larvae can be assigned to 4 different development stages, i.e. stages I, II, morphological features, S. canarium larvae can be assigned to 4 different development stages, i.e. stages I, II, hatching, and only metamorphosed when settlement cues (sediments from its natural habitat and 15 mM KCl) were introduced. They showed a short period of metamorphic competence, and no spontaneous metamorphosis was observed. Morphological changes and larval behaviors at the onset and during metamorphosis are also described.